Utilization of Durability Criterion to Develop Automotive Components - Ricardo,Luiz Carlos H. (2010)
Today the automotive companies must reduce the time to development of new products with improvement in performance, durability and low cost reductions where possible. To achieve this goal the carmakers need to improve the design criterion of car systems like body, chassis and suspension components. This paper will present a review of the techniques used in the automotive industry regarding durability before mentioned systems. The paper will present the procedures to obtain the spectrum loading to use in finite element analysis and the validation in laboratory and proving grounds.